Implementasi Pembelajaran Berdiferensiasi pada Materi IPS Peserta Didik SMP Budi Karya Natar - Dyanti Mahrunnisya; Kharisma Idola Arga; Veranda Amelia Putri; Heny Syntia (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This research aims to find out the implementation of differentiated learning in the independent curriculum and to find out the advantages and disadvantages of differentiated learning in the independent curriculum on social studies material at Budi Karya Natar Junior High School. The type of research used is field research and uses a descriptive approach. The Objects in this study were Budi Karya Natar Junior High School students. The data collection techniques used are observation, interview and documentation. While the data analysis technique uses data using data reduction, data presentation and conclusion drawing and verification. The results showed that the implementation of differentiated learning on social studies material has been applied at Budi Karya Natar Junior High School and differentiated learning requires careful preparation. The advantages of differentiated learning are that learning is more varied, with varied learning of course students do not get bored quickly, teachers and students are actively involved in learning. While the disadvantages of this differentiated learning are that students have not been able to adapt well because differentiated learning must adjust students' interests, learning profiles and learning readiness.